2020
DOI: 10.1111/apa.15063
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral facial nerve palsy in children in a Borrelia high‐endemic area, a retrospective follow‐up study

Abstract: Acute peripheral facial nerve palsy (FNP) is a well-described cranial nerve dysfunction of the seventh cranial nerve. The facial nerve carries motor fibres to the facial musculature, efferent secretory fibres to the lacrimal and salivary glands as well as afferent sensory fibres from the anterior two-thirds of the tongue and the external auditory canal. The onset of FNP is normally acute and causes inability to control facial muscles on the affected side. The annual incidence of FNP in children has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…4,10 A study from Stockholm, Sweden, showed an even higher prevalence (58%) of LNB, with a peak in October. 3 Two more Swedish studies (Gothenburg city with 10 surrounding municipalities and Kalmar County) also showed a higher LNB incidence during June-November, with a peak in August. European and Swedish guidelines recommend LP as a standard procedure when managing children with PFP.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…4,10 A study from Stockholm, Sweden, showed an even higher prevalence (58%) of LNB, with a peak in October. 3 Two more Swedish studies (Gothenburg city with 10 surrounding municipalities and Kalmar County) also showed a higher LNB incidence during June-November, with a peak in August. European and Swedish guidelines recommend LP as a standard procedure when managing children with PFP.…”
Section: Discussionmentioning
confidence: 92%
“…27 However, other studies have shown that 14%-32% of children with BPFP had no CSF pleocytosis and that patients with LNB had negative CSF Bb antibodies, particularly when LP was performed early in the course of the disease. 3,13,15 Therefore, negative CSF Bb antibodies or the absence of pleocytosis do not necessarily rule out a diagnosis of LNB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations